Preparation and Characterization of a Eutectic Mixture of Fenofibric Acid and Nicotinic Acid and Evaluatuion of In Vivo Antihyperlipidemic Activity - Deni Anggraini; Hulwa Salsabila; Salman Umar; Yufri Aldi; Erizal Zaini (Science and Technology Indonesia, 2022)
Fenofibric Acid (FA) is classified under Biopharmaceutical Classification System (BCS) class II due to its poorly soluble in water and high permeability. The present study aimed to prepare the eutectic mixture of FA with nicotinic acid (NA) and characterize its solid state properties and in vitro dissolution rate, along with its in vivo antihyperlipidemic activity. Solvent drop grinding was the method chosen to prepare the eutectic mixture of FA and NA. Solid-state properties were evaluated using thermal analysis Differential Scanning Calorimetry (DSC), crystallographic analysis Powder X-Ray Diffraction (PXRD), FT-IR spectroscopic analysis, and Scanning Electron Microscopy (SEM). To examine in vivo antihyperlipidemic activity, 16 male Swiss Webster rats were injected with 1% hyperlipidemia-inducing solution, followed by the oral administration of 9.45 mg/kg FA and NA (equivalent to 9.45 mg/kg FA), after which the decrease in cholesterol levels was measured. Two-way ANOVA was used to evaluate the data, followed by Duncan’s multiple range test (95% confidence interval). The results proved that FA formed the eutectic mixture with NA at a molar ratio of 6:4. The eutectic mixture of FA-NA had a better solubility and in vitro dissolution rate compared to intact FA, which also led to notably improved antihyperlipidemic activity.